Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/ese3.419
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the seepage characteristics of bituminous coal under the conditions of liquid nitrogen fracturing

Abstract: In coalbed methane (CBM) exploitation, liquid nitrogen (LN2) fracturing has attracted much attention as a promising and effective means to enhance coal seam permeability. Considering the bituminous coal in the Xutuan coal mine of Anhui Province, China, the permeability characteristics of coal samples under different pressure and stress conditions, and a single LN2 treatment and cyclic fracturing conditions were studied. Additionally, an evaluation of the macroscopic cracking behavior of coal was carried out. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The ultralow temperature of LN 2 induces temperature gradients and strong thermal stresses , in coal and rock masses and causes deformation between rock and mineral particles, freezing of pore fluids, and frost heave. Severe thermal shock causes physical changes to the walls of fractures, prevents the complete closure of hydraulic and thermally induced fractures, and thermally induces microcracks that are orthogonal to hydraulic cracks. , Because of the large differences between the thermal properties of the matrix and those of the internal mineral particles, freezing and thawing result in heterogeneous deformation and promote the initiation of new cracks. , The width, density, and connectivity of cracks in the coal increase considerably on both macro and micro levels. The initial pores and cracks in the matrix are destroyed, and a main fracture network is created. Figures and show the microscopic features of coal fractures.…”
Section: Ln2 Fracturing Coal Rock Mass In the Field Of Oil And Gas Ex...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ultralow temperature of LN 2 induces temperature gradients and strong thermal stresses , in coal and rock masses and causes deformation between rock and mineral particles, freezing of pore fluids, and frost heave. Severe thermal shock causes physical changes to the walls of fractures, prevents the complete closure of hydraulic and thermally induced fractures, and thermally induces microcracks that are orthogonal to hydraulic cracks. , Because of the large differences between the thermal properties of the matrix and those of the internal mineral particles, freezing and thawing result in heterogeneous deformation and promote the initiation of new cracks. , The width, density, and connectivity of cracks in the coal increase considerably on both macro and micro levels. The initial pores and cracks in the matrix are destroyed, and a main fracture network is created. Figures and show the microscopic features of coal fractures.…”
Section: Ln2 Fracturing Coal Rock Mass In the Field Of Oil And Gas Ex...mentioning
confidence: 99%
“…125,126 Because of the large differences between the thermal properties of the matrix and those of the internal mineral particles, freezing and thawing result in heterogeneous deformation and promote the initiation of new cracks. 127,128 The width, density, and connectivity of cracks in the coal increase considerably on both macro and micro levels. 129−131 The initial pores and cracks in the matrix are destroyed, and a main fracture network is created.…”
Section: Ln 2 Fracturing Coal Rock Mass In the Fieldmentioning
confidence: 99%
“…Due to coal anisotropy, a coal sampleÕs sensitivity to axial pressure and confining pressure is different. Effective stress is difficult for describing accurately the effect of stress variations in different directions of heterogeneous coal on its permeability (Chen et al, 2019). Generally, when a coal body is in the elastic stage, the confining pressure will control directly the opening of seepage channel (Zou et al, 2015).…”
Section: Response Characteristics Of Permeability To Axial Deviatoric Stressmentioning
confidence: 99%
“…As the injection pressure increases, the penetration rate is exponentially increasing. 27 In summary, a lot of research has been reported on the law of hydraulic fracturing crack propagation and permeability. However, there are few studies on the large-scale stress transfer after hydraulic fracturing in low-permeability coal seams and the investigation of gas drainage effects.…”
Section: Introductionmentioning
confidence: 99%